Laughter of the 19th century – a handful of reflections on the scope of the concept and the state of research - Kita, Jarosław; Korybut-Marciniak, Maria; Agnieszka Gralak (Laughter, humour, satire, 2024)
At first impression, it would seem that in the 19th century. Poles deprived of their own statehood, experiencing the defeats of successive national uprisings and the trauma associated with it, may have been far from humorous. Rather, the emotional perception of the era brings to mind images of suffering, discord, rebellion, sadness and longing. And yet Poles, during the period of building their national identity, dynamically changing reality under the influence of social, civilization, modernization, economic and demographic changes, did not give up their sense of humor. It was precisely humor, the ability to hold witty conversations and funny retorts that were a valued feature of the inhabitants of the Polish lands. Humor and satire allowed them to tame a difficult reality and sometimes took the form of resistance to the authoritarian systems of the partitioning authorities. Laughter was a tool to express a whole range of emotions: from joy and acceptance to irony, mockery, derision and negation. It was an important and valued component of “sociability,” or the interaction of people with each other in 19th century daily life.The authors of the articles in this collection prove precisely that the 19th century was not without humor. They try to seek answers to the question, what was the laughter of the century? The considerations contained in the pages of the book indicate that it was, above all, a laughter that kept the spirits up, a therapeutic laughter, a compensatory laughter, a laughter that marred pain, a laughter that tamed what was foreign, threatening, difficult to accept. Certainly, the volume is just a fraction in uncovering the “smiling face of the era,” but it should have an inspiring effect on researchers of Polish society under partition.